Some Localization Properties of the Lp Continuous Wavelet Transform. (2nd January 2018) - Medina, Juan Miguel; Cernuschi-Frías, Bruno
ABSTRACT: We shall prove some simultaneous localization or concentration inequalities for the continuous wavelet transform. We will also show that simultaneous localization in the scale-time(space) is impossible, in the sense that the scale sections of the support of wavelet transform of a nonnull L p -function can not have finite Lebesgue measure. Finally, some properties of the support of continuous wavelet transform of band-limited functions are studied.